Striving to Be King of Mobile Mountains: Communication and Organizing Through Digital Fitness Technology. Issue 2 (15th March 2017) - Smith, William Roth; Treem, Jeffrey
Abstract : This study considers fitness-tracking applications as settings for communicative performances. Qualitative interviews and observations with 41 users of a cycling-focused fitness application revealed communicative themes of qualifying, social sharing, and withholding. Users also assessed other members through social-group comparing and upward comparing. This study develops theory by revealing how individuals use the technology to communicate about their physical acts, and how the context of use facilitates organizing processes. We argue that use of this fitness application extends our understanding of how communication can constitute a community of practice (CoP; Brown & Duguid, 1991; Lave & Wenger, 1991). Primarily, the hybrid online/offline nature of Strava complicates the traditional understanding of communication and CoPs.